Trajectories of sleep disturbance and self-management of chronic conditions during COVID-19 among middle-aged and older adults - Minjee Kim; Lauren Rogers; Stephanie Batio; Julia Y. Benavente; Morgan Bonham; Pauline Zheng; Rebecca M. Lovett; Stacy C. Bailey; Mary J. Kwasny; Daniela P. Ladner; Sherry HY. Chou; Jeffrey A. Linder; et al. (Scientific Reports)
Abstract The COVID-19 pandemic has had a widespread impact on sleep quality, yet little is known about the prevalence of sleep disturbance and its impact on self-management of chronic conditions during the ongoing pandemic. To evaluate trajectories of sleep disturbance and their associations with one’s capacity to self-manage chronic conditions. A longitudinal cohort study linked to 3 active clinical trials and 2 cohort studies with 5 time points of sleep data collection (July 15, 2020–May 23, 2022). Adults living with chronic conditions who completed sleep questionnaires for two or more time points. Trajectories of self-reported sleep disturbance across 5 time points. Three self-reported measures of self-management capacity, including subjective cognitive decline, medication adherence, and self-efficacy for managing chronic disease. Five hundred and forty-nine adults aged 23 to 91 years were included in the analysis. Two-thirds had 3 or more chronic conditions; 42.4% of participants followed a trajectory of moderate or high likelihood of persistent sleep disturbance across the study period. Moderate or high likelihood of sleep disturbance was associated with age < 60 (RR 1.57, 95% CI 1.09, 2.26, P = 0.016), persistent stress (RR 1.54, 95% CI 1.16, 2.06, P = 0.003), poorer physical function (RR 1.57, 95% CI 1.17, 2.13, P = 0.003), greater anxiety (RR 1.40, 95% CI 1.04, 1.87, P = 0.03) and depression (RR 1.63, 95% CI 1.20, 2.22, P = 0.002). Moderate or high likelihood of sleep disturbance was also independently associated with subjective cognitive decline, poorer medication adherence, and worse self-efficacy for managing chronic diseases (all P < 0.001). Persistent sleep disturbance during the pandemic may be an important risk factor for inadequate chronic disease self-management and potentially poor health outcomes in adults living with chronic conditions. Public health and health system strategies might consider monitoring sleep quality in adults with chronic conditions to optimize health outcomes.